AI-LED PRODUCTIVITY GROWTH IN INDIA: TOWARDS VIKSIT BHARAT 2047 - Dr. Jyoti Ainapur; Shradha Andur; B Manju; Anirudh; Shridhar Mankari (International Educational Journal of Science and Engineering, 2026)
Artificial Intelligence (AI) is reshaping global economic structures by significantly enhancing productivity and enabling innovation-driven growth. In the Indian context, AI adoption is accelerating across sectors such as IT and services, financial services, manufacturing, healthcare, and agriculture, thereby influencing economic output and efficiency. This study investigates the role of AI in enhancing economic productivity through a longitudinal comparative sectoral analysis (2015–2025) using secondary data from the World Bank, NITI Aayog, OECD, McKinsey Global Institute, and the Reserve Bank of India. Statistical tools including Pearson correlation analysis, ordinary least squares regression, and one-way ANOVA are employed on a continuous eleven-year dataset. The findings reveal a very strong positive correlation (r = 0.945) between AI adoption and productivity growth, with AI explaining approximately 89.2% of productivity variation (R² = 0.892). ANOVA results (F = 11.69, p < 0.05) confirm significant inter-sectoral differences. AI is projected to contribute 500–600 billion to India’s GDP by 2035, with the highest productivity gains in technology-intensive sectors. The study concludes that a strategic, inclusive, and sector-specific AI policy framework is essential to achieve sustainable economic growth and realize the Viksit Bharat @ 2047 vision.